Pranoprofen Nanoparticles With Poly(L-Lactide)-b-Poly(Ethylene Glycol)-b-Poly(L-Lactide) as the Matrix Toward Improving Ocular Anti-inflammation - Luo, Yang; Yang, Lu; Feng, Peipei; Qiu, Haofeng; Wu, Xujin; Lu, Shuwei; Zhou, Mi; Xu, Long; Zhu, Yabin (Frontiers in Bioengineering and Biotechnology, 2020)
The nanotechnology using biodegradable polymer carriers with good biocompatibility and bioabsorbability has been much studied and applied in drug delivery system and biomedical engineering. In this work, the triblocked oligomer poly(L-lactide)-b-poly(ethylene glycol)-b-poly(L-lactide) (PLEL) with the molecular weight of 20.0 KDa was firstly synthesized. Its chemistry was characterized with hydrogen nuclear magnetic resonance (1H-NMR) spectrum and Fourier transform infrared (FTIR) spectroscopy. Subsequently, the nanoparticles (NPs) of PLEL and pranoprofen (PF) loaded PLEL were prepared with the average particle size of (151.7 ± 5.87) nm using the method of emulsion solvent evaporation. The formula and drug releasing profile were characterized by transmission electron microscope (TEM), dynamic light scattering (DLS) and ultraviolet spectrophotometer (US). In vitro cytotoxicity assays and in vivo ophthalmic tests were performed to measure the safety and efficacy of the formulations. The results showed that PF NPs relieved the cytotoxicity of pure PF and eliminated the ophthalmic irritation. The drug encapsulated in nanoparticles displayed long-lasting releasing and good anti-inflammation efficiency in animal eyes. Therefore, we concluded that the present formula (PF NPs) could provide sustained drug releasing with good treatment effect on eye inflammation, which will be a promising administration in ophthalmology in future.